1990
DOI: 10.1159/000238762
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ototoxicity of Ribostamycin, Dactimicin, Dibekacin, Kanamycin, Amikacin, Tobramycin, Gentamicin, Sisomicin and Netilmicin in the Inner Ear of Guinea Pigs

Abstract: Nine aminoglycoside antibiotics, ribostamycin (RSM), dactimicin (DAC), dibekacin (DKB), kanamycin (KM), amikacin (AMK), netilmicin (NTL), tobramycin (TOB), gentamicin (GM) and sisomicin (SISO) were administered intramuscularly to guinea pigs for 4 weeks, and ototoxicity and drug concentration in the inner ear fluid were determined. RSM and DAC showed the weakest ototoxicity against the cochlea and vestibular organs. AMK and KM were more toxic to cochlea than vestibular organs. DKB, TOM, GM and SISO were equall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…Currently, effective bacteriocidal therapy using gentamicin hinges upon either intravenous infusion or intramuscular administration [16] . Parenteral administration of gentamicin has been associated with side effects that include mainly nephrotoxicity and ototoxicity [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, effective bacteriocidal therapy using gentamicin hinges upon either intravenous infusion or intramuscular administration [16] . Parenteral administration of gentamicin has been associated with side effects that include mainly nephrotoxicity and ototoxicity [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…T h e uptake o f G M in inner ear tissues is rapid, in contrast to its s l o w e l i m i n a t i o n [22]. G M is also the a m i n o g l y c o s i d e antibiotic w i t h the h i g h e s t ototoxic potential [16]. This is due to the cationic character o f the m o l e c u l e u n d e r p h y s i o l o g i c a l p H conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Pharmacokinetic studies have revealed that aminoglycoside antibiotics are slowly eliminated [7,16,20] and accumulate in the inner ear, especially in the outer hair cells [8,9,14], Deiter's and Hensen's cells and the stria vascularis [10], as well as in type I cells of the vestibule [13]. Although the concentration of aminoglycoside antibiotics in the peri-and endolymph can be correlated with that in the plasma, the level in plasma is much higher than in inner ear fluids [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When used in the treatment of cow mastitis, adequate withdrawal periods are required to avoid the occurrence of amikacin residues in the milk (Chen et al, 2012). This is important because amikacin has earlier been reported to have potential ototoxicity (Kitasato, Yokota, Inouye, & Igarashi, 2004;Zawilla et al, 2007) and nephrotoxicity (Luft et al, 1978;Serrano & Silva, 2006).…”
Section: Introductionmentioning
confidence: 99%